Effect of Fluoride-containing Mouthrinses on the Translucence of Resin Modified Glass Ionomer Cements - Garcia, Patrícia Petromilli Nordi Sasso [UNESP]; Corona, Silmara Aparecida Milori; Dibb, Regina Guenka Palma; Chimello, Daniela Thomazatti; Catirse, Alma Blásida Elizaur; Freitas, Emaneula Maurício [UNESP] (ABM, ABC, ABPol, 2002)
The aim of this in vitro study was to assess the effect of different fluoride-containing mouthrinses on the translucence of resin-modified glass ionomer cements, as a function of the restorative material used, the fluoride-containing solution employed and the time of immersion. Disks were prepared (10 mm × 2 mm) with the modified glass ionomer cements Vitremer (3M) and Fuji II LC (GC Co.), and immersed in three fluoride-containing solutions: Fluordent Reach (Johnson & Johnson), Fluorgard (Colgate-Palmolive) and Oral B (Gillette do Brasil Ltda). Translucence was measured with electrophoresis equipment (JOUAN) after different immersion times. The results obtained were submitted to ANOVA and Tukey's test, and a statistically significant decrease was observed in the translucence of the materials after immersion in the fluoride-containing solutions. Fuji II LC demonstrated the lowest alteration in translucence, independently of the solution employed. Fluorgard was the fluoride-containing mouthrinse that promoted the highest alteration. It can be concluded that the fluoride-containing mouthrinses influenced the translucence of the resin-modified glass ionomer cements.
Keywords: translucence; resin modified glass ionomer cement; fluoride-containing mouthrinses